Factors Associated With Poor Linkage to Human Immunodeficiency Virus Care Among Index Clients and Sex Partners Receiving Human Immunodeficiency Virus Assisted Partner Services in Kenya. Issue 9 (September 2020) - Wamuti, Beatrice; Contesse, Marielle G.; Maingi, Peter; Macharia, Paul; Abuna, Felix; Sambai, Betsy; Ng'ang'a, Anne; Spiegel, Hans; Richardson, Barbra; Cherutich, Peter; Bukusi, David; Farquhar, Carey
Abstract : Introduction: Human immunodeficiency virus (HIV) assisted partner services (aPS) has been recommended as a strategy to increase HIV case finding. We evaluated factors associated with poor linkage to HIV care among newly diagnosed HIV-positive individuals (index clients) and their partners after receiving aPS in Kenya. Methods: In a cluster randomized trial conducted between 2013 and 2015, 9 facilities were randomized to immediate aPS (intervention). Linkage to care—defined as HIV clinic registration, and antiretroviral therapy (ART) initiation were self-reported. Antiretroviral therapy was only offered to those with CD4 less than 500 during this period. We estimated linkage to care and ART initiation separately for index clients and their partners using log-binomial generalized estimating equation models with exchangeable correlation structure and robust standard errors. Results: Overall, 550 index clients and 621 sex partners enrolled, of whom 46% (284 of 621) were HIV-positive. Of the 284, 264 (93%) sex partners returned at 6 weeks: 120 newly diagnosed and 144 whom had known HIV-positive status. Among the 120 newly diagnosed, only 69% (83) linked to care at 6 weeks, whereas among the 18 known HIV-positive sex partners not already in care at baseline, 61% (11) linked. Newly diagnosed HIV-positive sex partners who were younger and single were less likely to link to care ( P < 0.05 for all). Conclusion: Only two thirds of newly diagnosed, and known HIV-positive sex partners not in care linked to care after receiving aPS. The HIV aPS programs should optimize HIV care for newly diagnosed HIV-positive sex partners, especially those who are younger and single. Abstract : A study of clients in cluster randomized trial in Kenya found that only two thirds of newly diagnosed human immunodeficiency virus (HIV)-positive and known HIV-positive sex partners not previously linked to care who received HIV assisted partner notification services eventually linked to HIV care.